2017
DOI: 10.2298/vsp150612162k
|View full text |Cite
|
Sign up to set email alerts
|

The importance of impulse oscillometry in bronchial provocation testing in confirming the diagnosis of asthma in male army recruits

Abstract: Background/Aim. Impulse oscillometry (IOS) is a technique valid for measuring the lung function in obstructive lung diseases and bronchial provocation tests. However, no consensus exists for its use. The aim of the study was to assess impulse oscillometry sensitivity for detection of early airways changes during bronchial provocation testing and to compare with changes obtained with spirometry and bodyplethysmography in male army recruits. Methods. Male military recruits were submitted to bronchial provocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Similar to Koruga et al 22 and Mousa and Kamal, 25 Nair et al 26 patients with previous diagnosis of asthma and 61 healthy subjects. The asthma group was older (mean age 49 years vs mean age 28 years in the control group).…”
Section: Results Of Individual Studiesmentioning
confidence: 62%
See 4 more Smart Citations
“…Similar to Koruga et al 22 and Mousa and Kamal, 25 Nair et al 26 patients with previous diagnosis of asthma and 61 healthy subjects. The asthma group was older (mean age 49 years vs mean age 28 years in the control group).…”
Section: Results Of Individual Studiesmentioning
confidence: 62%
“…Only one study reported R5–R20. 24 The values of the test were reported in different units with Mori et al 24 and Mendonça et al 23 reporting results in cmH 2 O/L/s, Nair et al 26 and Mousa and Kamal the % predicted values and Koruga et al 22 and Nikkhah et al 28 in kPa/L/s.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations